Mapping Use of a Self-directed On-line Heart Disease Education Program onto Health Learning Outcomes: A Study of Post-Heart Attack Learners - Meg Wise; Gi Woong Yun; Bret Shaw (Adult Education Research Conference, 2000)
We correlated 25 heart patients’ changes in four behaviors to usage of behavior themes and three on-line learning activities. Information correlated negatively; communications correlated positively; and interactive planning showed a positive trend with changing behaviors. These findings challenge on-line educators to transcend information provision and offer more opportunities that integrate social interaction and planning.